Preferential CO oxidation in H2 over Au/La2O3/Al2O3 catalysts: The effect of the catalyst reduction method - Lakshmanan, Pandian; Park, Eun Duck (Catalysts, 2018)
We investigated the influence of the reduction method on the preferential oxidation of CO in H2 (CO-PROX) over Au/La2 O3/Al2 O3 catalysts. An Au/La2 O3/Al2 O3 sample, prepared using deposition–precipitation with urea, was reduced by chemical reduction with NaBH4 or glycerol. Several techniques, such as diffuse-reflectance infrared Fourier-transform spectroscopy after CO adsorption (CO-DRIFTS), X-ray photoelectron spectroscopy (XPS) and transmission electron microscopy (TEM) were used to characterize the catalysts. Additionally, the catalysts were examined by in situ DRIFTS during methanol decomposition. The results reveal that the reduction method affects the average particle size and electronic state of gold, as well as the characteristics of the CO–Au0 interactions. The best CO-PROX performance was observed for the catalyst chemically reduced using NaBH4 with a NaBH4/Au molar ratio of 35. This catalyst contained gold particles with size of ~4 nm, for which the XPS binding energy was lower than that of metallic gold.
Keywords: Au/La2O3/Al2O3; Chemical reduction; CO-PROX; Effect of reduction method; Glycerol; Gold; NaBH4